Sensitivity Analysis of Flutter of A Two-Degree of Freedom Linear Aeroelastic System - Riccy Kurniawan (Jurnal Teknik Mesin (Sinta 3), 2011)
This paper deals with the problem of the aeroelastic stability of a typical aerofoil section with two degrees of freedom induced by unsteady aerodynamic loads. A method is presented to model the unsteady lift and pitching moment acting on a two dimensional typical aerofoil section, operating under attached flow conditions in an incompressible flow. Starting from suitable generalisations and approximations to aerodynamic indicial functions, the unsteady loads due to an arbitrary forcing are represented in a state-space form. From the resulting equations of motion, the flutter speed is computed through stability analysis of a linear state-space system. The sensitivity analysis of the aeroelastic stability boundaries to the structural parameter is evaluated. The results show that the parameter with the greatest influence on flutter speed is the center of gravity.